β-secretase inhibitor; a promising novel therapeutic drug in Alzheimer’s disease - Menting, Kelly Willemijn; Claassen, Jurgen A. H. R. (Frontiers in Aging Neuroscience, 2014)
Alzheimer’s disease (AD) and vascular dementia are responsible for up to 90% of dementia cases. According to the World Health Organization (WHO), a staggering number of 35.6 million people are currently diagnosed with dementia. Blocking disease progression or preventing AD altogether is desirable for both social and economic reasons and recently focus has shifted to a new and promising drug: the β-secretase inhibitor. Much of AD research has investigated the amyloid cascade hypothesis, which postulates that AD is caused by changes in amyloid beta (Aβ) stability and aggregation. Blocking Aβ production by inhibiting the first protease required for its generation, β-secretase/BACE1, may be the next step in blocking AD progression. In April 2012, promising phase I data on inhibitor MK-8931 was presented. This drug reduced Aβ CSF levels up to 92% and was well tolerated by patients. In March 2013 data was added from a one week trial in 32 mild to moderate AD patients, showing CSF Aβ levels decreased up to 84%. However, BACE1 inhibitors require further research. First, greatly reducing Aβ levels through BACE1 inhibition may have harmful side effects. Second, BACE1 inhibitors have yet to pass clinical trial phase II/III and no data on possible side effects on AD patients are available. And third, there remains doubt about the clinical efficacy of BACE1 inhibitors. In moderate AD patients, Aβ plaques have already been formed. BACE1 inhibitors prevent production of new Aβ plaques, but hypothetically do not influence already existing Aβ peptides. Therefore, BACE1 inhibitors are potentially better at preventing AD instead of having therapeutic use.